To live and let die: Food, famine, and administrative violence in Democratic Kampuchea, 1975–1979. (September 2015) - Tyner, James A.; Rice, Stian
Abstract: Between 1975 and 1979 approximately two million people died in the Cambodian genocide. We argue that the mass violence that transpired during this period was a manifestation of the Khmer Rouge's attempt to make life. Through a focus on the production of both violence and vulnerability we direct attention to the contradictory policies and practices forwarded by the Khmer Rouge that were designed to maximize life through the maximization of death. Specifically, we consider the mass starvation that accompanied the genocide as a structure of violence; we forward the argument that the rationing of food constitutes a calculated yet contradictory policy, namely that food rations represent in material form an inner contradiction of fostering life and disallowing life. Subsequently, the policy of forced rations—which imposed a particular space of vulnerability on Cambodia's population—resulted in massive loss of life through starvation and disease that were not the unintended side-effects of poor research, poor planning, or poor implementation on behalf of the Khmer Rouge, but rather were the necessary consequences of a proto-capitalist form of state-building. Highlights: Forwards a conception of administrative violence. Provides a theoretical linkage of direct and structural violence. Develops a theoretical understanding of killing and letting die within a context of mass violence. Contributes to the study of famine within the context of genocide. Provides an empirical case study of the Cambodian genocide.